Discovery of Active Bacterial Microbiome in Human Brain Tissue: Implications for Neurodegenerative Diseases and Depression - Pratiwi Ratih Halimatus Sya'diah; Eka Cahya Muliawati (Science Journal Get Press, 2024)
The concept of a sterile human brain has recently been challenged by emerging evidence suggesting the presence of microbial DNA and components within brain tissue. This study aimed to investigate the presence and disease-specific patterns of microbial signatures in human brains affected by Alzheimer’s disease and depression, compared to healthy controls. Using 16S rRNA sequencing on post-mortem brain samples, we detected microbial DNA in all groups, with notable differences in diversity and composition. Alzheimer’s brains exhibited reduced microbial richness and were enriched in genera such as Cutibacterium and Streptococcus, which may contribute to neuroinflammation and amyloid aggregation. Depressive brains showed increased abundance of Eggerthella, potentially influencing neurotransmitter metabolism and systemic inflammatory pathways, while control brains had higher prevalence of Lactobacillus and Bifidobacterium, consistent with neuroprotective roles. These findings support the emerging “brain microbiome” concept and suggest that low-abundance microbial communities may reflect disease-associated processes or interactions via the microbiota-gut-brain axis. While causality and microbial viability remain to be established, the study highlights the potential relevance of brain-associated microbes in neurodegenerative and psychiatric disorders and provides a foundation for future experimental and translational research exploring microbiome-targeted diagnostic and therapeutic strategies.